2022
DOI: 10.1186/s12891-022-05137-8
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association between knee osteoarthritis and depressive symptoms: evidence from a nationwide population-based cohort

Abstract: Background Both knee osteoarthritis (KOA) and depressive symptoms (DS) are major public health issues affecting the quality of life. This study aimed to examine the association between KOA and DS. Methods Data were gathered from the China Health and Retirement Longitudinal Study in 2011–2015 which surveyed middle-aged to elderly individuals and their spouses in 28 provinces in China. An adjusted Cox proportional hazards regression model was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…As well, those suffering from a long standing or chronic major depressive disorder [11] may encounter an unrelenting cycle of pain and disability rather than any simple unidirectional cause effect association [15]. Other research shows that delaying the opportunity to intervene on the presence of depression regardless of cause or type is likely to do more harm than good in as many as 50 percent or more of osteoarthritis cases [16], especially where perceptions of any cumulative or perceived discrimination prevail [2,5].…”
Section: Resultsmentioning
confidence: 99%
“…As well, those suffering from a long standing or chronic major depressive disorder [11] may encounter an unrelenting cycle of pain and disability rather than any simple unidirectional cause effect association [15]. Other research shows that delaying the opportunity to intervene on the presence of depression regardless of cause or type is likely to do more harm than good in as many as 50 percent or more of osteoarthritis cases [16], especially where perceptions of any cumulative or perceived discrimination prevail [2,5].…”
Section: Resultsmentioning
confidence: 99%
“…People with long-term MSK conditions are likely to report feeling anxious or depressed when compared to healthy individuals (9, 10), and there is evidence to support the bidirectional relationship. For example, anxiety and depression might heighten sensation of pain associated with MSK conditions, while persistent pain might worsen mental health (9,(11)(12)(13). For patients with both physical and mental health conditions, higher rates of morbidity, healthcare utilisation and poorer quality of life have been observed (14).…”
Section: Introductionmentioning
confidence: 99%
“…According to Shuang Zheng et al, depression is found in 25.4% of symptomatic knee OA patients with an annual incidence of 11.2% among them [ 5 ]. Han Lu et al explored that there is a bidirectional association between depression and knee OA [ 6 ]. The progression of OA is deleterious to the quality of life, working capacity, health, and social welfare [ 7 ].…”
Section: Introductionmentioning
confidence: 99%